2012
DOI: 10.1159/000342469
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Macro- and Micronutrients in Slovenian Adolescents: Comparison with Reference Values

Abstract: Background: Data on a nationally representative dietary intake in Central Europe is lacking. We investigated the diet of adolescents in Slovenia. Methods: Dietary habits were assessed using a food frequency questionnaire (n = 2,661), and present nutrition was assessed using a 3-day weighted dietary protocol (n = 197) for validation purposes. Dietary intake was calculated and compared with Central European [German (D), Austrian (A), and Swiss (CH); D-A-CH] recommendations and World Health Organization/Food and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…Moreover, the intake of calcium was much lower than the recommended amounts in both groups (712 and 776 mg/d in overweight and non-overweight respectively, vs. the recommended 1100-1200 mg/d) [20], which is in line with a study of Slovenian adolescents [30].…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…Moreover, the intake of calcium was much lower than the recommended amounts in both groups (712 and 776 mg/d in overweight and non-overweight respectively, vs. the recommended 1100-1200 mg/d) [20], which is in line with a study of Slovenian adolescents [30].…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…Mean dietary intake of vitamin D from food alone ranged from 1.1 to 8.2 μg/day. In a recent study on dietary habits of Slovenian adolescents, we found that they consumed only 4 µg vitamin D/day instead of a recommended 20 µg/day [22,38]. Contrary to the most developed countries, both vitamin D fortification and supplementation policies in pregnancy have not been implemented in Slovenia, and the use of dietary supplements containing vitamin D remains an individual's decision.…”
Section: Discussionmentioning
confidence: 99%
“…The result of these insufficient attentions is either insufficient or excessive diet. For example, Fidler (2012) showed the in appropriation of adolescents’ dietary habits in Slovenia were associated with the growth problems. In China, the average quantity of protein consumption in children and adolescents in 1991 to 2009 has decreased and caused the deduction of weight and height among adolescents ( Lopes et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%